Digital Attendance System Implementation, Employee Competence, and Work Discipline on Government Employee Performance - Fitra Haerul Jamal; Mahmud Mahmud; Lilis Marlina (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the determinants of civil servant performance by evaluating the impact of the digital attendance system, employee competencies, and work discipline—both individually and collectively—at the Dompu Regency Finance and Asset Management Agency (BPKAD). Research Method: Using a quantitative causal design, primary data were collected through a questionnaire distributed to the entire population of 77 employees (saturation sampling). The data were then analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. Results and Discussion: Digital attendance systems and work discipline have been shown to have a positive and significant impact on performance. Conversely, employee competence has been shown to have no significant impact. Collectively, this model explains 52.2% of the variation in performance. These findings confirm that the power of technological oversight and rule compliance can compensate for weaknesses in individual technical capacity. Implications: In practical terms, agency leaders are advised to prioritize E-HRM investments to ensure reliable infrastructure for monitoring and enforcing disciplinary regulations. Future research is recommended to expand the sample scope to include other Regional Government Work Units (SKPDs). Originality: This study integrates the Information System Success Model and the 21st-century digital competency framework into a single holistic Socio-Technical System analytical model for the public financial management sector.